Institutional strengthening model of oil palm independent smallholder in Riau and Jambi Provinces, Indonesia - Sapta Raharja (Heliyon, 2020)
The oil palm independent smallholder (farmer) is one of the important actors in maintaining the continuity of the production cycle in the oil palm agro-industry supply chain in Indonesia. Various fundamental problems faced by the independent smallholder are related to land legality as well as their limited ability to manage good agricultural practices, access funds and information on current prices, and use of quality and agricultural production facilities. The institutional strengthening of the independent smallholder requires attention and support from government and other business actors in the supply chain of the oil palm agro-industry. This study aims to obtain a model of institutional strengthening through the application of the enrich seven steps of soft system methodology. The assumptions that must be fulfilled in strengthening this institution were described. The institutional strengthening model was developed in three stages, i.e., the establishment of smallholder corporations, the establishment of independent cooperatives, and the revitalization of the Indonesian oil palm independent smallholder association. Various individual strengthening actors were investigated and then integrated. The suggested institutional strengthening model involved cooperatives, smallholder farmers groups, and the oil palm mill, supported by regulatory, financial, and input provider agencies with a mutual partnership program.